Survival of the Amanah Learning Center (ALeC) Institution in Realizing an ‘Kampung Inggris’ - Saifullah, Muhammad; Fadlilah, Sayyidatul (At-Taqaddum, 2022)
The housing complex around the campus is a laboratory for lecturers and students as the most effective embodiment of the tri dharma of higher education. This tri dharma is based on campus programs called environmental development, where the campus feels responsible for students living in villages around the campus. One pattern of bringing the campus world closer to the community is how to empower human resources around the campus. This article aims to describe the role of the State Islamic Religious College in empowering the Kampoeng Amanah Social Institution (Amanah Learning Center), a village whose mission is to make the village an English-language village. Research and service methods are carried out in a participatory manner, namely through social analysis of community potential and assisting them in realizing a language village pilot based on Islamic values. The assistance stages are through entrance, Diagnosis, Action Planning, Intervention, Evaluation and Reflection. The results of this research and service have brought about the reorganization of ALeC management based on a map of the human resource potential of Kampoeng Amanah who has a background in education, economics and religion. This assistance has also resulted in a sustainable ALeC program design and the implementation of these programs for ALeC's survival in creating a language village based on Islamic values.The housing complex around the campus is a laboratory for lecturers and students as the most effective embodiment of the tri dharma of higher education. This tri dharma is based on campus programs called environmental development, where the campus feels responsible for students living in villages around the campus. One pattern of bringing the campus world closer to the community is how to empower human resources around the campus. This article aims to describe the role of the State Islamic Religious College in empowering the Kampoeng Amanah Social Institution (Amanah Learning Center), a village whose mission is to make the village an English-language village. Research and service methods are carried out in a participatory manner, namely through social analysis of community potential and assisting them in realizing a language village pilot based on Islamic values. The assistance stages are through entrance, Diagnosis, Action Planning, Intervention, Evaluation and Reflection. The results of this research and service have brought about the reorganization of ALeC management based on a map of the human resource potential of Kampoeng Amanah who has a background in education, economics and religion. This assistance has also resulted in a sustainable ALeC program design and the implementation of these programs for ALeC's survival in creating a language village based on Islamic values.